Correction: Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals (BMC Palliative Care, (2022), 21, 1, (71), 10.1186/s12904-022-00963-y) - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Bazata, Jeremias; Schildmann, Eva; Ostgathe, Christoph (BMC Palliative Care, 2022)
Following the publication of the original article [1], the author reported that the given name and family name of all authors were erroneously transposed. The author group has been updated above and the original article [1] has been corrected.
CRIS-Team Scopus Importer:2022-09-09

Correction to: The quality of care of the dying in hospital—next-of-kin perspectives (Supportive Care in Cancer, (2020), 10.1007/s00520-020-05465-2) - Heckel, Maria; Vogt, Annika R.; Stiel, Stephanie; Radon, Johannes; Kurkowski, Sandra; Goebel, Swantje; Ostgathe, Christoph; Weber, Martin (Supportive Care in Cancer, 2020)
The surname and name of Christoph (name) Ostgathe (surname) are reversed.
CRIS-Team Scopus Importer:2020-06-05

COVID-19: Challenges and solutions for the provision of care to seriously ill and dying people and their relatives during SARS-CoV-2 pandemic - perspectives of pandemic response team members: A qualitative study on the basis of expert interviews (part of PallPan) - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Kriesen, Ursula; Schneider, Carolin; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph (Palliative Medicine, 2022)
Background: During the SARS-CoV-2 pandemic's initial waves, bans on visiting and isolation measures placed limits on providing services for seriously ill and dying people and their relatives. Pandemic response teams at governmental level (macro), at federal state and municipal level (meso) and in healthcare facilities (micro) played their role in pandemic management procedures. Aim: To explore pandemic-related challenges and solutions of pandemic response teams regarding the provision of care to seriously ill and dying people and their relatives. Findings were to be integrated into a national strategy (PallPan). Design: Semi-structured expert interviews (10/2020-2/2021) analysed via structured content analysis. Setting/Participants: We interviewed 41 members, who discussed the work of 43 German pandemic response teams (micro n = 23; meso n = 20; no members were available at macro level) from 14 German federal states. Results: Twenty-nine of 43 teams took account of the needs of seriously ill and dying. Their main challenges resulted from pandemic-related legal requirements in hospitals and long-term care facilities. The implementation of such was in the remits of the meso level. Dysfunctional or non-existent communication between the levels was reported to be challenging. To foster patient-related solutions the micro level pandemic response teams supported individual decisions to enable patient-relative contact for example, visiting and saying goodbye outside, meeting via digital solutions. Conclusions: Pandemic response teams evidently struggled to find appropriate solutions to ease pandemic-related impact on the care of seriously ill and dying patients and their relatives. We recommend bringing palliative care expertise on board.
CRIS-Team WoS Importer:2022-06-24
Keywords: Qualitative research; palliative care; COVID-19; public health; SARS-CoV-2

COVID-19 pandemic response teams: organization, competencies, and challenges-understanding and using structural realities - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Krisen, Ursula; Stellmacher, Silke; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2022)
Background and aim. Germany has a federal state system. Pandemic response teams are key instruments of pandemic management. The aim of this article is to describe the structures and powers of pandemic response teams that were explored during a study on the care of the critically ill and dying in times of a pandemic (Pall Pan). The focus is on health-related pandemic response teams on the national state level (macrolevel) and federal and community level (mesolevel) as well as pandemic response teams in healthcare facilities (microlevel).
CRIS-Team WoS Importer:2022-05-13

Digital health transition in rheumatology: A qualitative study - Müehlensiepen, Felix; Kurkowski, Sandra; Krusche, Martin; Mucke, Johanna; Prill, Robert; Heinze, Martin; Welcker, Martin; Schulze-Koops, Hendrik; Vuillerme, Nicolas; Schett, Georg; Knitza, Johannes (International Journal of Environmental Research and Public Health, 2021)
The global COVID-19 pandemic has led to drastic changes in the management of patients with rheumatic diseases. Due to the imminent risk of infection, monitoring intervals of rheumatic patients have prolonged. The aim of this study is to present insights from patients, rheumatologists, and digital product developers on the ongoing digital health transition in rheumatology. A qualitative and participatory semi-structured fishbowl approach was conducted to gain detailed insights from a total of 476 participants. The main findings show that digital health and remote care are generally welcomed by the participants. Five key themes emerged from the qualitative content analysis: (1) digital rheumatology use cases, (2) user descriptions, (3) adaptation to different environments of rheumatology care, and (4) potentials of and (5) barriers to digital rheumatology implementation. Codes were scaled by positive and negative ratings as well as on micro, meso, and macro levels. A main recommendation resulting from the insights is that both patients and rheumatologists need more information and education to successfully implement digital health tools into clinical routine.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Chronic disease; Content analysis; Digital health; EHealth; Fishbowl discussion; Patient perspective; Qualitative research; Remote care; Rheumatology; Telemedicine

Expert-approved best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care (SedPall) - Ostgathe, Christoph; Bausewein, Claudia; Schildmann, Eva; Bazata, Jeremias; Handtke, Violet; Heckel, Maria; Klein, Carsten; Kremling, Alexander; Kurkowski, Sandra; Meesters, Sophie; Seifert, Andreas; Torres Cavazos, Jorge; et al. (BMC Palliative Care, 2023)
Background: The use of sedative drugs and intentional sedation in end-of-life care is associated with clinical, ethical and legal challenges. In view of these and of the issue’s great importance to patients undergoing intolerable suffering, we conducted a project titled SedPall (“From anxiolysis to deep continuous sedation – Development of recommendations for sedation in palliative care“) with the purpose of developing best practice recommendations on the use of sedative drugs and intentional sedation in specialist palliative care and obtaining feedback and approval from experts in this area. Design: Our stepwise approach entailed drafting the recommendations, obtaining expert feedback, conducting a single-round Delphi study, and convening a consensus conference. As an interdisciplinary group, we created a set of best practice recommendations based on previously published guidance and empirical and normative analysis, and drawing on feedback from experts, including patient representatives and of public involvement participants. We set the required agreement rate for approval at the single-round Delphi and the consensus conference at ≥80%. Results: Ten experts commented on the recommendations’ first draft. The Delphi panel comprised 50 experts and patient and public involvement participants, while 46 participants attended the consensus conference. In total, the participants in these stages of the process approved 66 recommendations, covering the topics “indications”, “intent/purpose [of sedation]”, “decision-making”, “information and consent”, “medication and type of sedation”, “monitoring”, “management of fluids and nutrition”, “continuing other measures”, “support for relatives”, and “team support”. The recommendations include suggestions on terminology and comments on legal issues. Conclusion: Further research will be required for evaluating the feasibility of the recommendations’ implementation and their effectiveness. The recommendations and the suggested terminology may serve as a resource for healthcare professionals in Germany on the use of sedative drugs and intentional sedation in specialist palliative care and may contribute to discussion on the topic at an international level. Trial Registration: DRKS00015047 (German Clinical Trials Register)
CRIS-Team Scopus Importer:2023-09-15
Keywords: Community-based participatory research; Empirical research; Hypnotics and sedatives; Palliative care; Practice guidelines; Terminal care

Hospital end-of-life care: Families' free-text notes - Kurkowski, Sandra; Radon, Johannes; Vogt, Annika R.; Weber, Martin; Stiel, Stephanie; Ostgathe, Christoph; Heckel, Maria (BMJ Supportive & Palliative Care, 2020)
Background: Palliative care strives to improve quality of life for patients with incurable diseases. This approach includes adequate support of the patients' loved ones. Consequently, loved ones have personal experiences of providing end-of-life care for their next. This is a resource for information and may help to investigate the loved ones' perspectives on need for improvements. Aim: To identify further quality aspects considered important by loved ones to improve the quality of care at the end of life as an addition to quantitative results from the Care of the Dying Evaluation for the German-speaking area (CODE-GER) questionnaire. Design: Within the validation study of the questionnaire â € Care of the Dying Evaluation' (CODETM) GER, loved ones were asked to comment (free text) in parallel on each item of the CODE-GER. These free-text notes were analysed with the qualitative content analysis method by Philipp Mayring. Setting/participants: Loved ones of patients (n=237), who had died an expected death in two university hospitals (palliative and non-palliative care units) during the period from April 2016 to March 2017. Results: 993 relevant paragraphs were extracted out of 1261 free-text notes. For loved ones, important aspects of quality of care are information/communication, respect of the patient's and/or loved one's will, involvement in decision-making at the end of life (patient's volition) and having the possibility to say goodbye. Conclusions: It is important for loved ones to be taken seriously in their sorrows, to be informed, that the caregivers respect the patients' will and to be emotionally supported. Trial registration number: This study was registered at the German Clinical Trials Register (DRKS00013916).
CRIS-Team Scopus Importer:2020-12-11
Keywords: hospital care; quality of life; service evaluation; social care; supportive care; terminal care

Identifying the need for specialized palliative care in adult cancer patients - Development and validation of a screening procedure based on proxy assessment by physicians and filter questions - Ostgathe, Christoph; Wendt, Kim N.; Heckel, Maria; Kurkowski, Sandra; Klein, Carsten; Krause, Stefan; Fuchs, Florian; Bayer, Christian M.; Stiel, Stephanie (BMC Cancer, 2019)
Background: One challenge in caring for cancer patients with incurable disease is the adequate identification of those in need for specialized palliative care (SPC). The study's aim was to validate an easy to use phenomenological screening tool. Methods: The German tool is based on the National Comprehensive Cancer Network (NCCN) Palliative Care guidelines and contains ten items in five domains that focus e.g. on diagnosis, functional status, complications, comorbidities, and palliative care relevant problems such as symptom management, distress, and support of family and team members. Sum score ranges from 0 to 14 (no need to great need). Assessment to identify SPC needs was done in university hospital wards between 1 and 08/2017 by health care professionals on admission of the patient if the disease was incurable and expected prognosis < 12 months. The Integrated Palliative Outcome Scale (IPOS, staff version), an outcome assessment instrument for palliative care that consists of ten items, served as external criterion; in sub samples inter-rater/test-retest were performed. Results: Data from 208 patients with incurable disease and life expectancy < 12 months (54.8% female; average age 63.5 years, range 21-96) were assessed using the tool. The tool has good convergent validity; the correlation between the sum scores of IPOS and our tool showed a significant and substantial effect. The sum score was independent of the patient's age, gender and primary diagnosis. Patients who already were in contact with SPC had significantly higher screening scores than patients without. With a cut point of ≥ 5, 80.8% of the screened patients were in need for SPC. Cronbach's alpha was α =.600. Rater agreement (inter-rater, test-retest) varied between single items. Correlation coefficients showed significant substantial effects. Conclusions: This is the first validation of a screening procedure in German language identifying SPC needs of adult patients with advanced cancer and the first using filter questions as a pre-screening. Proxy assessment of SPC needs by physicians in cancer care settings is feasible and the suggested tool presents a valid instrument to trigger a PC consultation. Trial registration: The study was not registered.
CRIS-Team Scopus Importer:2019-07-16
Keywords: Cancer; Delivery of health care; Needs assessment; Palliative care; Psychometric properties

“It’s pretty much flying blind in the home care setting”: A qualitative study on the influence of home care specific circumstances on sedation in specialist palliative home care - Meesters, Sophie; Bazata, Jeremias; Handtke, Violet; Gehrmann, Jan; Kurkowski, Sandra; Klein, Carsten; Bausewein, Claudia; Schildmann, Eva (Palliative Medicine, 2022)
Background: Existing data on sedation at the end of life indicate challenges in the home care setting, leading to deviations from guidelines or non-provision of sedation. Aim: As part of the “SedPall” study, we aimed to explore circumstances in specialist palliative home care, which influence the practice of sedation. Design: Semi-structured qualitative interviews (n = 59) and two focus groups (n = 4, n = 5). Recruitment took place via contact persons. We thematically analyzed the transcripts with the Framework Approach, using MAXQDA 2018.2. Setting/participants: Physicians, nurses, and other members of the multiprofessional team from 10 palliative care units and seven home care teams. Results: Participants reported home care specific circumstances that can be categorized into three interrelated topics. (1) Lack of 24/7 on-site availability, (2) active involvement of the family, (3) challenges regarding teamwork and multidisciplinarity. Participants drew different conclusions from the reported circumstances regarding the feasibility of different types of sedation at home: While some reported to generally use all types of sedation, others stated that some types of sedation are not feasible in home care, for example deep sedation until death. Most participants questioned the applicability of existing sedation guidelines in the home care setting. Conclusion: Our data indicate that sedation practices might currently follow the healthcare professional’s attitude or service policy rather than the patient’s need. To avoid hospital admission in manageable cases and ensure that home care specific best practice standards are met, existing guideline recommendations have to be adapted and supplemented by additional supporting measures specific for the home care setting.
CRIS-Team Scopus Importer:2022-10-28
Keywords: ambulatory care; Deep sedation; hypnotics and sedatives; palliative care; qualitative research

More Barriers than Bridges - Research in Times of the GDPR - Kurkowski, Sandra; Ziegler, Kerstin; Jäger, Christian; Torres Cavazos, Jorge; Heckel, Maria; Klein, Carsten; Ostgathe, Christoph (Zeitschrift für Palliativmedizin, 2022)
CRIS-Team WoS Importer:2022-03-18

Possible age-related differences in healthcare professionals’ perspectives on younger and older patients’ autonomy and decision-making in the context of sedation in specialised palliative care: exploratory secondary qualitative content and linguistic conversation analysis of interviews with healthcare professionals - Kurkowski, Sandra; Heckel, Maria; Pfaller, Larissa; Peters, Joachim; Jeremias, Bazata; Eva, Schildmann; Ostgathe, Christoph (BMC Palliative Care, 2022)
Background Chronic illnesses and multi-morbidity can threaten competence and independence, particularly in old age. Autonomy becomes increasingly important in the context of sedation, as in this case medication leads to (further) changes of consciousness. The study aimed to identify possible age-related differences in the perspectives of healthcare professionals on patients’ autonomy, in the context of sedation in specialised palliative care. Method Secondary analysis of interviews with healthcare professionals, analysed by qualitative content and linguistic conversation analysis. The interviews analysed span 51 healthcare professionals in specialised palliative care across 17 centres (adult inpatient and specialist palliative home care services) in Germany. Results The study shows that the perspectives of healthcare professionals on patients’ autonomy differs according to the age of the patient in the context of sedation in specialised palliative care. The different perspectives may lead to different ways of treating the patients, for example a greater space of autonomy and decision-making for younger patients. Conclusion In particular, measures that may restrict consciousness (e.g. sedation) and thus influence patients’ ability to fully exercise their autonomy and fully participate in decision-making require special attention by healthcare professionals with respect to possible influences on treatment, such as different perceptions by healthcare professionals based on the patient’s age or age-related stereotype
Keywords: End of life care; Palliative care; Age; Ageing; Autonomy; Qualitative content analysis; Linguistic conversation analysis

The quality of care of the dying in hospital—next-of-kin perspectives - Heckel, Maria; Vogt, Annika R.; Stiel, Stephanie; Radon, Johannes; Kurkowski, Sandra; Goebel, Swantje; Ostgathe, Christoph; Weber, Martin (Supportive Care in Cancer, 2020)
Purpose: Providing high-quality care for the dying is essential in palliative care. Quality of care can be checked, compared, and improved by assessing responses from bereaved next-of-kin. The objectives of this study are to examine quality of care in the last 2 days of life of hospitalized patients considering specific aspects of their place of care. Methods: The “Care of the Dying Evaluation” (CODE™) questionnaire, validated in German in 2018 (CODE-GER), examines quality of care for the patient and support of next-of-kin, allocating values between 0 (low quality) and 4 (high quality). The total score (0–104) is divided into subscales which indicate support/time given by doctors/nurses, spiritual/emotional support, information/decision-making, environment, information about the dying process, symptoms, and support at the actual time of death/afterwards. Next-of-kin of patients with an expected death in specialized palliative care units and other wards in two university hospitals between April 2016 and March 2017 were included. Results: Most of the 237 analyzed CODE-GER questionnaires were completed by the patient’s spouse (42.6%) or children (40.5%) and 64.1% were female. Patients stayed in hospital for an average of 13.7 days (3–276; SD 21.1). Half of the patients died in a specialized palliative care unit (50.6%). The CODE-GER total score was 85.7 (SD 14.17; 25–104). Subscales were rated significantly better for palliative care units than for other wards. Unsatisfying outcomes were reported in both groups in the subscales for information/decision-making and information about the dying process. Conclusion: The overall quality of care for the dying was rated to be good. Improvements of information about the dying process and decision-making are needed. Trial registration: DRKS00013916
CRIS-Team Scopus Importer:2020-05-22
Keywords: Caregivers; Death; Outcome assessment (healthcare); Palliative care; Quality; Surveys

The virtual fishbowl: Bringing back dynamic debates to medical conferences - Muehlensiepen, Felix; Mucke, Johanna; Krusche, Martin; Kurkowski, Sandra; Bendzuck, Gerlinde; Koetter, Ina; Lemarié, Vanessa; Grahammer, Manuel; Heinze, Martin; Schulze-Koops, Hendrik; Knitza, Johannes (Annals of the Rheumatic Diseases, 2020)
CRIS-Team Scopus Importer:2021-04-19
Keywords: COVID-19; economics; health care; health care; health services research; outcome and process assessment; quality indicators

Wishes of nursing home residents for their dying - Kurkowski, Sandra; Heckel, Maria; Volland-Schüssel, Käte (Zeitschrift für Gerontologie und Geriatrie, 2018)
BACKGROUND: Institutions of inpatient geriatric care are dependent on specific and practicable concepts for the terminal care of old people, because residential and nursing homes are places for the last phase of life. OBJECTIVE: The objective of this study was to identify the wishes of residents for their dying who live in a residential or nursing home. METHOD: The analysis was based on 10 semi-structured expert interviews with residential and nursing home residents. The interviews were evaluated using the method of qualitative summarizing content analysis. Based on the grounded theory a procedure was selected in which data were collected, prepared and evaluated in parallel. RESULTS AND DISCUSSION: Residents expressed, inter alia, the following wishes: not to receive life-prolonging measures, not to have pain, not to be in need of care or bedridden, to receive affection while dying and to find forgiveness and reconciliation as well as to die peacefully in the residential and/or nursing home. In addition, there were a variety of wishes, which, due to their diversity make a unified approach to the palliative care of older people in residential and/or nursing homes impractical. The study showed that residents are thinking about dying and/or death, have desires for their dying and are also willing to talk about it. The recording and the translation of these wishes and also the response to the residents' fears can be achieved by the implementation of a palliative culture and the training of employees.
EVALuna2:204778